Built Beyond American Borders: Comparing the Construction and Maintenance of the School-to-Prison Pipeline in the United States and New Zealand - Beck, Emily (New Zealand Sociology, 2025)
The school-to-prison pipeline (STPP) is the process by which children of colour are disproportionately funnelled from education institutions into the criminal justice system. This article investigates how the STPP was developed through unfolding systems of oppression in both the United States and New Zealand. Harsh disciplinary measures and zero tolerance policies were implemented in both countries, facilitating a rise in exclusionary discipline for minority youth. Compounded by negative police contact, state care involvement, and structural inequality, children who face disciplinary measures in school are significantly more likely to become justice involved. The analysis presented here displays how minority children in the United States and New Zealand experience long-lasting detrimental outcomes due to the systemic racism and ongoing oppression embedded within education systems in both countries. By uncovering the underlying contributors to the pipeline, options to dismantle it can be explored.